2004
DOI: 10.1080/09638280410001712387
|View full text |Cite
|
Sign up to set email alerts
|

Adults with cerebral palsy benefit from participating in a strength training programme at a community gymnasium

Abstract: This study adds to the accumulating evidence that strength training can be beneficial for people with cerebral palsy by demonstrating benefits for adults with cerebral palsy and high support needs who are subject to decline in physical function associated with the ageing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 26 publications
3
51
0
3
Order By: Relevance
“…Only a few studies dealing with physical activity in adults were found, and they focused on strength training [13,14]. The training increased strength and improved…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies dealing with physical activity in adults were found, and they focused on strength training [13,14]. The training increased strength and improved…”
Section: Discussionmentioning
confidence: 99%
“…Ageing in combination with overuse and/or immobilisation are considered as contributory factors to the deterioration [3,5,12]. Physical training may counteract the impairments, but only a few studies report from the effects of physical training in the adult population with CP [13,14]. More studies shows that different kinds of physical activity are beneficial for children with CP [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…18 A hand-held dynamometer (Nicholas Manual Muscle Tester, Lafayette, LA, USA) was used to assess isometric strength of the targeted muscles for each participant. 19 …”
Section: Outcome Measuresmentioning
confidence: 99%
“…Strengthening of these muscles is therefore often a goal in the treatment of adults with CP. In 2 studies, 10 weeks of progressive resistance training (RT) were found to increase muscle strength in adults with CP (5,6). Other studies on children with CP also reported good effect on muscle strength after RT (4,7,8).…”
Section: Introductionmentioning
confidence: 99%